Profile of urgent and emergency care in a northwestern Paraná base (Research, Society and Development, 2021)
Objective: To analyze the epidemiological profile of the occurrences of a decentralized base of SAMU 192 in a municipality in the Northwest of Paraná. Methodology: The present study is retrospective and, analytical, epidemiological study with a quantitative approach. For this purpose, the forms of care provided between January and March 2019 were used. Data were collected regarding the sociodemographic characteristics of the victims and the types of urgent and emergency care provided by the professionals. The present study was submitted to and approved by the Research Ethics Committee of the State University of Paraná, respecting the ethical precepts of Resolution 466/2012 and 510/2016 of the National Health Council, under approval protocol No. 3,313,124 Results: It was observed that of the 941 medical records analyzed 653 (69.4%) due to clinical causes, 196 (20.8%) due to trauma, 62 (6.6%) psychiatric occurrences and 30 (3.2%) gynecological causes -obstetric. It showed a statistically significant difference in the comparison between the sexes, in relation to the nature of the occurrence and the type of ambulance available for care. In addition, men served by SAMU were 1.5 times more likely to demand assistance from a USA. Conclusions: The analysis showed the need to develop intersectoral health promotion and prevention actions related to information about the characteristic signs and symptoms of urgency and emergency.